Expression of transient receptor potential vanilloid 4 (TRPV4) in NERD vs normal control and association with PH study and manometry parameter - Azis, Nazihah (2018)
Background Non erosive reflux Disease (NERD) has emerged as a real entity in the spectrum of gastroesophageal reflux disease (GERD).It may potentially represent the most common manifestation of reflux disease. Although numerous studies had been performed on NERD,none of the the studies had explored the expression of TRPV4 as a causative factor and the link between pH study and manometry. This knowledge is beneficial for new targeted treatment. Methodology This was a prospective study that was done on NERD and control patients from March 2017 until November 2017. A total of 55 patients - 39 NERD and 16 control patients were investigated. All patients had undergone EGD and multiple biopsies were taken. Notably, erosive esophagitis patients were excluded. Apart from that, the patients also went through pH study and manometry. Results The result from this research we showed that TRPV4 was expressed in both NERD and control patients. No association was discovered between TRPV4 and NERD, as well as among pH study, manometry and endoscopic features. Futhermore, TRPV4 was found to be higher in cells from the normal group as compared to the NERD group. Notably, p-value was insignificant but this may be caused by small sample size Conclusion This study was performed to determine the association between TRPV4 and NERD. No significant association was revealed between the expression of of TRPV 4 and the NERD group. Similarly, other parameters from pH study, manometry and endoscopic finding also did not show any significant association with TRPV4.